Alterations in hyperpolarization-activated cyclic nucleotidegated cation channel (HCN) expression in the hippocampus following pilocarpine-induced status epilepticus - Oh, Yun-Jung (Korean Society for Biochemistry and Molecular Biology, 2012)
To understand the effects of HCN as potential mediators in the pathogenesis of epilepsy that evoke long-term impaired excitability; the present study was designed to elucidate whether the alterations of HCN expression induced by status epilepticus (SE) is responsible for epileptogenesis. Although HCN1 immunoreactivity was observed in the hippocampus, its immunoreactivities were enhanced at 12 hrs following SE. Although, HCN1 immunoreactivities were reduced in all the hippocampi at 2 weeks, a re-increase in the expression at 2-3 months following SE was observed. In contrast to HCN1, HCN 4 expressions were un-changed, although HCN2 immunoreactive neurons exhibited some changes following SE. Taken together, our findings suggest that altered expressions of HCN1 following SE may be mainly involved in the imbalances of neurotransmissions to hippocampal circuits; thus, it is proposed that HCN1 may play an important role in the epileptogenic period as a compensatory response. [BMB Reports 2012; 45(11): 635-640]